The effect of psychopathology on quality of life and disability in patients with fibromyalgia - Akay, Esra; Şenormancı, Ömer; Eröksüz, Rıza; Şenormancı, Güliz; Demirci, Onur Okan (The European Research Journal, 2022)
Objectives: The aim of the study was to investigate the relationship between pain, depression, anxiety, somatic amplification and alexithymia in patients with fibromyalgia syndrome (FMS), and on quality of life and disability. As a secondary goal, the predictors of disability were evaluated. Methods: Participants were 112 female patients aged 18 and over, applied to the outpatient clinic of University of Health Sciences Bursa Yüksek İhtisas Training and Research Hospital Medical Ecology and Hydroclimatology department and diagnosed with FMS according to ACR 2016 Revised Fibromyalgia Diagnosis Criteria. The Sociodemographic Data Form, Visual Analog Scale (VAS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Toronto Alexithymia Scale (TAS-20), Somatosensory Amplification Scale (SSAS), Fibromyalgia Impact Questionnaire (FIQ) and Health Survey Questionnaire Short Form (SF-36) were applied to each participant. All data were analyzed with correlation and linear regression. Results: Increased pain intensity, depression, anxiety, somatic amplification, "difficulty identifying feeling" and "difficulty describing feelings" dimensions of alexithymia were found related to lower quality of life and increased disability. Depression, somatic amplification, and pain severity were defined as the predictors of disability in FMS. Conclusions: Psychiatric examination of FMS patients especially in terms of depression, anxiety, alexithymia and somatic amplification as well as their physical complaints can be beneficial to minimize disability and increase the quality of life. To our best knowledge, this is the first study to show somatic amplification as a predictor of disability in FMS patients. Further studies will be helpful to understand this relationship.